Measuring trade‐offs that matter: assessing the impact of a new electronic cross‐match policy on the turnaround time and the cross‐match workload efficiency. Issue 12 (27th May 2014) - Lin, David M.; Goldfinger, Dennis; Lu, Qun; Wallace, Bridget; Kosaka‐Nguyen, Dawn; Wood, Alisa; Porter, Bethany; Bumerts, Pamela; Jeffery, Rebecca; Fang, Amy; Stalcup, Irene; Penaflorida, Tracy; et al.
<x xml:space="preserve">Abstract</x> Background Our traditional cross‐match (XM) policy generated a significant number of XM units that were never issued. To minimize the unnecessary XM workload, we proposed a new policy where orders eligible for the electronic XM (EXM) are pended until orders to issue red blood cells (RBCs) are received. To address concerns that this new policy might unduly delay blood availability, we conducted a study to assess whether the new policy was noninferior to the traditional policy with regard to the turnaround time (TAT). Study Design and Methods We monitored the TAT and XM workload efficiency (XM‐to‐issue [C : I] ratio) for a total of 8 weeks split between the two policies' periods. The primary outcome was the proportion of RBC issue requests that was turned around in less than 12 minutes. Results Fifty percent (1133 of 2265) of issue requests were turned around in 12 minutes or less under the traditional policy compared to 43.9% (975 of 2223) under the new policy (absolute difference of 6.1%; 95% confidence interval [CI], 3.2%‐9.1%; p < 0.001). The adjusted overall median TAT was slower by 1 minute (13 min vs. 14 min, p < 0.001) but the adjusted C : I ratio was better (1.00 vs. 1.15; p < 0.001) under the new policy. Conclusion Our study showed that the impact of the new policy on the TAT was not inferior to the traditional policy. Since the median TAT of 14 minutes under the new policy met the published benchmarks, the trade‐off between delays in the TAT and efficiency gains in the XM workload remained acceptable for patient care.